Cultured gill-derived Neoparamoeba pemaquidensis fails to elicit amoebic gill disease (AGD) in Atlantic salmon Salmo salar - Morrison, RN; Crosbie, PBB; Cook, MT; Mark Adams; Barbara Nowak (2005)
Amoebic gill disease (AGD) affects the culture of Atlantic salmon Salmo salar in the southeast of Tasmania. The disease is characterised by the presence of epizoic Neoparamoeba spp. in association with hyperplastic gill tissue. Gill-associated amoebae trophozoites were positively selected by plastic adherence for culture in seawater, where they proliferated using heat-killed E. coli as a nutrient source. One isolate of gill-harvested amoebae designated NP251002 was morphologically consistent to N. pemaquidensis under light, fluorescence and transmission electron microscopy. Rabbit anti-N. pemaquidensis antiserum bound to NP251002, and N. pemaquidensis small subunit (SSU) ribosomal DNA (18S rDNA) was detected in NP251002 genomic DNA preparations using PCR. A high degree of similarity in the alignment of the NP251002 18S rDNA PCR amplicon sequence with reference isolates of N. pemaquidensis suggested conspecificity. While short-term culture (72 h) of gill-harvested amoebae does not affect the capacity of amoebae to induce AGD, Atlantic salmon challenged with NP251002 after the trophozoites had been 34 and 98 d in culture exhibited neither gross nor histological evidence of AGD. It is not known if NP251002 were avirulent at the time of isolation, had down-regulated putative virulence factors or virulence was inhibited by the culture conditions. Therefore, the time in culture could be a limiting factor in maintaining virulence using the culture technique described here. Â© Inter-Research 2005.